Dance Intervention Affects Social Connections and Body Appreciation Among Older Adults in the Long Term Despite COVID-19 Social Isolation: A Mixed Methods Pilot Study - Hansen, Pil; Main, Caitlin; Hartling, Liza (Frontiers in Psychology, 2021)
The ability of dance to address social isolation is argued, but there is a lack of both evidence of such an effect and interventions designed for the purpose. An interdisciplinary research team at University of Calgary partnered with Kaeja d’Dance to pilot test the effects of an intervention designed to facilitate embodied social connections among older adults. Within a mixed methods study design, pre and post behavioral tests and qualitative surveys about experiences of the body and connecting were administered to thirteen participants along with test instruments of loneliness and body appreciation. In the short-term, no significant changes were found on quantitative tests. Exploratory analysis revealed intervention improvements on individual body appreciation questions only. This indication of change was strongly supported by converging qualitative data and identified as relating to: increased connection through task-based collaboration, increased awareness of interpersonal boundaries, and a shift to experiencing the body as responsive. These indications of increased relational capacity were deemed likely to cause further impact in the long term. Examining this possibility and the subsequently arisen factor of Covid-19 risks and restrictions, test instruments were administered again to ten participants four and five months after the intervention. A significant increase in loneliness was found. Despite this negative impact of Covid-19 isolation, several positive intervention changes remained detectable and some continued to increase over time. 70% of the participants, who made new social contacts during the intervention and later sought continued contact, improved significantly across all body appreciation measures over the full study. The qualitative data from the last two time-points revealed both consistent values and new, negative changes. While these preliminary findings speak to the durability of intervention changes, they also identify areas of urgent priority to help older adults restore embodied relational capacity that has declined during Covid-19. Within the limitations of a small-sample pilot study, converging mixed methods results support the hypothesis that dance interventions designed for the purpose can positively affect the social inclusion of older adults. Although we recommend further study, these promising results also indicate that dance interventions can help older adults recover from pandemic isolation.